The Japanese model of education: a holistic and integrated approach - Nasser, Youcef (International Institute of Islamic Thought (IIIT), 2026)
This book offers a comprehensive exploration of Japan’s educational evolution, tracing its roots from the Tokugawa and Meiji periods to its contemporary philosophies and global influence. Through a historical, philosophical, and comparative lens, it examines how Japan’s education system emerged from a synthesis of moral tradition, intellectual rigor, and social purpose. The chapters collectively reveal how Buddhist and Confucian ethics, holistic educational principles, and a strong teaching profession have shaped Japan’s pursuit of both personal cultivation and national progress. Finally, by extending these insights to the Arab-Islamic context, the book underscores the universal relevance of integrated, value-based education as a cornerstone of cultural renewal and sustainable development.